Strength of mesh augmented rotator cuff repair - Teoh Yong Jiak (2019)
There are several options to repair rotator cuff tear, such as anchor repair, mesh augmentation repair, patch augmentation repair and superior capsular reconstruction. The common treatment of the rotator cuff tear is surgical repair, but post-operative re-tear of the rotator cuff happens frequently. Hence, it is important to improve the repair technique through biomechanical performance. In this study, the objective is to evaluate the strength of the rotator cuff repair using surgical suture mesh and suture. Eight sheep shoulder specimens were used in the experiment, repaired with with a folded Premilene Mesh and the Ethibond Excel Polyester 2-0 suture, using double weaving mattress stitch (tendon side) and double weaving continuous suture (tuberosity side) for the repair. All specimens are mounted on the custom-designed fixture and then secured onto Instron 5566 machine for the ultimate failure load test and cyclic load test. For cyclic load test, specimens were loaded between 10N to 180 N at 8.33 mm/s for 3000 cycles. Gap formation were recorded every 500 cycles until it reaches 3000 cycles. Ultimate failure load test was conducted after cyclic load test. The mean gap formation and the mean ultimate failure load was 1.792 ± 0.122 mm and 421.96 ± 143.52 N respectively. The mode of failure of all eight shoulder specimens were suture pull-out through the greater tuberosity. Comparing to others study using different method for repairing rotator cuff tear, dual-row enveloped Premilene Mesh with double weaving mattress stitch and double weaving continuous suture repair is relatively stronger than existing single row anchors in ultimate failure load test but has bigger gap formation after 3000 cycles. In addition, this current method was also proven to be stronger than previous mesh repairs studies.